Molecular Characterization of Plant Volatile Compound Interactions with Cnaphalocrocis medinalis Odorant-Binding Proteins - Qi Qian; Xin Guo; Lingjie Wu; Jiarong Cui; Huiying Gao; Yajun Yang; Hongxing Xu; Zhongxian Lu; Pingyang Zhu (Plants, 2024)
Odorant-binding proteins (OBPs) play important roles in the insect olfactory system since they bind external odor molecules to trigger insect olfactory responses. Previous studies have identified some plant-derived volatiles that attract the pervasive insect pest Cnaphalocrocis medinalis (Lepidoptera: Pyralidae), such as phenylacetaldehyde, benzyl acetate, 1-heptanol, and hexanal. To characterize the roles of CmedOBPs in the recognition of these four volatiles, we analyzed the binding abilities of selected CmedOBPs to each of the four compounds, as well as the expression patterns of CmedOBPs in different developmental stages of C. medinalis adult. Antennaes of C. medinalis adults were sensitive to the studied plant volatile combinations. Expression levels of multiple CmedOBPs were significantly increased in the antennae of 2-day-old adults after exposure to volatiles. CmedOBP1, CmedOBP6, CmedPBP1, CmedPBP2, and CmedGOBP2 were significantly up-regulated in the antennae of volatile-stimulated female and male adults when compared to untreated controls. Fluorescence competition assays confirmed that CmedOBP1 could strongly bind 1-heptanol, hexanal, and phenylacetaldehyde; CmedOBP15 strongly bound benzyl acetate and phenylacetaldehyde; and CmedOBP26 could weakly bind 1-heptanol. This study lays a theoretical foundation for further analysis of the mechanisms by which plant volatiles can attract C. medinalis. It also provides a technical basis for the future development of efficient plant volatile attractants of C. medinalis.